THEOLOGY AND GENDER IN THE AFRICAN CONTEXT: AN EDITORIAL - Conradie, Ernst M. (Scriptura, 2004)
Most of the articles in this edition of Scriptura derive from a conference of the Theological Society of South Africa that was held at the Hammanskraal campus of the University of Pretoria from 20-22 June 2003. The topic of the conference was "Theology and gender in the African context".